Innovative Drugs to Target Renal Inflammation in Sepsis: Alkaline Phosphatase - Hümmeke-Oppers, Femke; Hemelaar, Pleun; Pickkers, Peter (Frontiers in Pharmacology, 2019)
Sepsis-related mortality roughly doubles when acute kidney injury (AKI) occurs and end stage renal disease is more common in sepsis-associated AKI survivors. So far, no licensed treatment for the prevention of AKI is available, however the data on alkaline phosphatase is promising and might change this. Sepsis-associated AKI is believed to be the result of inflammation and hypoxia combined. Systemic inflammation started by recognition of ‘pathogen-associated molecular patterns’ (PAMPs) such as lipopolysaccharide (LPS) which binds to Toll-like receptor 4 and leads to the production of inflammatory mediators. Due to this inflammatory process renal microcirculation gets impaired leading to hypoxia resulting in cell damage or cell death. In the process of cell damage so called ‘danger-associated molecular patterns’ (DAMPs) are released resulting in a sustained inflammatory effect. Apart from the systemic inflammation DAMPs and PAMPs also interact with receptors in the proximal tubule of the kidney causing a local inflammatory response leading to leukocyte infiltration and tubular lesions, combined with renal cell apoptosis and ultimately to acute kidney injury. In the longer-term, inflammation-mediated inadequate repair mechanism may lead to fibrosis and development of chronic kidney disease. Alkaline phosphatase (AP) is an endogenous enzyme that dephosphorylates and thereby detoxifies several compounds, including LPS. A small phase 2 clinical trial in sepsis patients showed that urinary excretion of tubular injury markers was attenuated and creatinine clearance improved in sepsis patients treated with AP. This renal protective effect was confirmed in a second small clinical phase 2 trial in sepsis patients with AKI. Subsequently, a large trial in sepsis patients with AKI was conducted using a human recombinant AP. In 301 patients no improvement of kidney function within 7 days after enrolment was observed, but kidney function was significantly better on day 21 and day 28 and all-cause 28-day mortality was significantly lower (14.4% in AP group versus 26.7% in the placebo group). Possible explanations of this lack of short-term kidney function improvement are discussed and potential effects of AP on renal repair mechanisms, including inflammation-mediated induction of fibrosis, that may explain the beneficial longer-term effects of AP are proposed.